Escultura em metal no século XX : poéticas, métodos e procedimentos - Mena, Ana, 1984- (2019)
In this studio we looked for the value of poetics, methods and procedures for the study of metal sculpture in the 20th century. Sculpture´s morphology was developed initially by the process of addition and later by the construction. Through the modeling in clay proceeded with the passage to bronze. With the paradigm shift in the early twentieth century, cast sculpture began to be realized through new materials such as iron, lead and cement. With the use of ferrous materials, iron and steel, and through cold and hot techniques, the procedure characteristic of modernist sculpture, construction, emerged. In this way the foundry and the construction contributed to the transition from Classicism to Modernism and later to Contemporaneity. The use by the sculptors of ferrous metals, especially of iron, has linked sculpture and technology over the years, serving growth and development as well as cultural creativity. Contemporary authors continue to use it as a means to develop techniques that express and answer current questions. From the reflection to the practice applied today, sculptors use a wide variety of processes in their work. Contemporary authors who work metals use it as a sculptural vehicle for the imagination, based on their properties. However, there are some questions: Have there been profound changes from modernity to contemporaneity in the study of metals? In contemporary times, the choice of forms remains the same as in the last century? Is the technology of metals used in the same way? In this sense these questions were the starting point of this investigation, since we traced a course in the sculptural production of modernism, national and international, through the problematization of some of the different ways of approaching the concept of sculpture that was developed during the twentieth century